Introgressing cry1Ac for Pod Borer Resistance in Chickpea Through Marker-Assisted Backcross Breeding - Kaur, Ajinder; Sharma, Urvashi; Singh, Sarvjeet; Singh, Ravinder; Vikal, Yogesh; Singh, Satnam; Malik, Palvi; Kaur, Khushpreet; Singh, Inderjit; Bindra, Shayla; Sarmah, Bidyut Kumar; Sandhu, Jagdeep Singh (Frontiers in Genetics, 2022)
The gram pod borer Helicoverpa armigera is a major constraint to chickpea (Cicer arietinum L.) production worldwide, reducing crop yield by up to 90%. The constraint is difficult to overcome as chickpea germplasm including wild species either lacks pod borer resistance or if possessing resistance is cross-incompatible. This study describes conversion of elite but pod borer-susceptible commercial chickpea cultivars into resistant cultivars through introgression of cry1Ac using marker-assisted backcross breeding. The chickpea cultivars (PBG7 and L552) were crossed with pod borer-resistant transgenic lines (BS 100B and BS 100E) carrying cry1Ac that led to the development of BC1F1, BC1F2, BC1F3, BC2F1, BC2F2, and BC2F3 populations from three cross combinations. The foreground selection revealed that 35.38% BC1F1 and 8.4% BC1F2 plants obtained from Cross A (PBG7 × BS 100B), 50% BC1F1 and 76.5% BC1F2 plants from Cross B (L552 × BS 100E), and 12.05% BC2F2 and 82.81% (average) BC2F3 plants derived from Cross C (PBG7 × BS 100E) carried the cry1Ac gene. The bioassay of backcross populations for toxicity to H. armigera displayed up to 100% larval mortality. BC1F1 and BC1F2 populations derived from Cross B and BC2F3 population from Cross C segregated in the Mendelian ratio for cry1Ac confirmed inheritance of a single copy of transgene, whereas BC1F1 and BC1F2 populations obtained from Cross A and BC2F2 population from Cross C exhibited distorted segregation ratios. BC1F1 plants of Cross A and Cross B accumulated Cry1Ac protein ranging from 11.03 to 11.71 µgg−1 in leaf tissue. Cry1Ac-positive BC2F2 plants from Cross C demonstrated high recurrent parent genome recovery (91.3%) through background selection using SSR markers and phenome recovery of 90.94%, amongst these 30% plants, were homozygous for transgene. The performance of BC2F3 progenies derived from homozygous plants was similar to that of the recurrent parent for main agronomic traits, such as number of pods and seed yield per plant. These progenies are a valuable source for H. armigera resistance in chickpea breeding programs.